Mental health practices in selected government agencies - Bonifacio, Mary Liza Madera (2007)
The study explored the mental health practices in selected government agencies namely, Department of Justice, Court of Appeals, Supreme Court, National Bureau of Investigation, and the University of the Philippines Manila. A total of 163 employees participated. The study used the descriptive method which involved qualitative and quantitative methods, using survey and focus group discussion. The results indicated that employees in the public workplace encounter various concerns and problem in the workplace. Top of these concerns is the lack of recognition of work compensated through salary. The majority of the participants did not seek counseling. But they expressed that they would like to have counseling services in their office.